AVL Boost Simulation of Engine Performance and Emission for Compressed Natural Gas Direct Injection Engine - Zahari, Taha; Teuku, Firsa; Raja Ariffin, Raja Ghazilla (Universiti Tenaga Nasional, 2014)
Natural gas is an alternative to gasoline as a fuel for automotive engines. The combustion of natural gas produces mainly water and CO2 and significantly less CO and UHC emissions. In many cases, CNG vehicles generate fewer exhaust and greenhouse gas emissions than their gasoline or diesel-powered counterparts. Internal combustion engines can be powered by natural gas without significant effort in production and distribution since raw natural gas needs minimal processing before distribution. In this research, a study of direct injected CNG engine is conducted. AVL Boost was used to simulate methane direct injection, CNG port injection and gasoline port injection in a four-cylinder spark ignition engine. Methane is used in place of CNG for simplicity. There appears to be a good approximation from initial tests since CNG comprise around 80-90% methane.